Implementasi Pendidikan Karakter dalam Kurikulum Sekolah Menengah Atas sebagai Upaya Pencegahan Radikalisme - Tarso, Tarso; Handika Suryatama; Surya Adi Saputra; Deny Hadi Siswanto (Jurnal Bersama Ilmu Pendidikan (DIDIK), 2025)
This study aims to analyze the implementation of character education in the curriculum at SMA Muhammadiyah Mlati as an effort to prevent radicalism. The research employs a phenomenological method with a descriptive qualitative approach. The subjects of the study include nine students from grades X, XI, and XII, as well as the principal, two teachers, and three parents as supporting informants. Data were collected through interviews, observations, and documentation and analyzed thematically. The findings indicate that SMA Muhammadiyah Mlati implements character education through the integration of the Merdeka Curriculum and the ISMUBA Curriculum. The principal plays a key role in setting policies, motivating teachers, and creating a conducive learning environment. Teachers serve as role models and facilitators in shaping students' character through classroom interactions. As the main actors, students are taught values such as discipline, honesty, and empathy through academic and extracurricular activities. Character education at this school also includes religious and nationalistic values as a strategy to prevent radicalism. However, challenges remain, including students' lack of awareness and varying understandings of character values. Therefore, collaboration among schools, teachers, students, and parents is essential to optimizing sustainable character education.